Self-Directed Learning as a Political Act: Learning Projects of Women on Welfare - Cynthia Lee Andruske (Adult Education Research Conference, 2000)
This paper explores self-directed learning of women on welfare in their transitions to paid work and education as political act, and expands the definition of self-directed learning to the political realm.